Trump's Trade Offensive and The Gulf Response: Navigating a New Era of US-Middle East Economic Relation - Fadhlia, Maudy Noor; Fahlevi, Zhillan Zhalila (UI Scholars Hub, 2025)
In 2025, the Trump administration implemented sweeping tariff measures as part of its